Bioethanol production at bank scale using national inputs: sugar cane and quebranta grape's yeast - De La Cruz Azabache, Mario Ricardo (2012)
The alcohol fuel, denatured anhydrous bioethanol or just bioethanol can be obtained from different renewable raw materials, such as substrates bearing simple sugars, starch and lignocellulose, requiring the use of specific microorganisms (biomass) that synthesize the organic matter contained therein. This work focuses on obtaining hydrated bioethanol (ethanol at 94,8 % by volume, just before azeotropic point) from sugar cane by using quebranta grape’s yeast, byproduct of Pisco-UNI process. The hydrated bioethanol obtained could then be used as a main input for the production of bioethanol (dehydration), biodiesel (transesterification), among others. The results demonstrated the desired objective satisfactorily, as well as achieved obtaining improvements in the process efficiency through pretreatment, both the sugar cane juice and the yeast used, allowing to have by this way a scientific basis for the design of an unconventional process to produce hydrated bioethanol.